Indicadores previdenciários antes e durante a pandemia em trabalhadores domésticos com base na teoria de stress de Seyle de 1956 - Oliveira, Renata Rocha de (2023)
Domestic work, in its slave history, encompassed by burdens, discrimination, abuse and invisibility, continues, even after 135 years of the abolition of slavery, in conditions far below expectations, triggering diseases such as the stress studied by Hans Selye, in 1956. The theory of Selye's Stress and its phases, alarm reaction (anxiety) and resistance phase (depression), lead many domestic workers to withdraw from activities temporarily or permanently. To this end, this thesis had as its main objective to study social security indicators in two moments, before and during the Covid-19 pandemic in domestic workers, using Social Security data and based on Selye's theory. Regarding the method, as it is a quantitative research, the collection took place in a secondary way – which are included in the Social Security database -, as well as the transformation of qualitative indicators into ranks, with non-parametric statistics. The population consisted of all domestic workers who obtained benefits granted by Social Security, as a form of maintenance assistance while they remained ill. A study of panel data using a pooled model was applied as a strategy, with the cut-off point in the month of enactment of Decree nº. 6 of March 2020, analyzing the existence, or not, of reflexes before or during the pandemic, in each one of the social security indicators in the study. In this way, a total of 12,118 observations were obtained, in which 12 statistical panel models were generated, capable of describing the behavior of the indicators, according to the occupational disease, in general and for separate periods. As a result of the models found, the occupational disease that stood out was depression, with three consistent models (general, before the pandemic and during the pandemic), which include the largest number of indicators among all models. Thus, it can be concluded that depression (2nd phase of the General Adaptation Syndrome - SGA) is the disease that most affected and still affects domestic workers throughout Brazil, impacted by the pandemic with job losses, discrimination, devaluation and remaining to be ignored by society and government.